The Effect of Note-Taking Method Toward Listening Ability at Second Semester at English Language Education Faculty of Teacher Training and Education University of Batanghari Jambi - Nurul Lidyanti; Wennyta Wennyta (JELT: Journal of English Language Teaching, 2020)
This research was aimed to find out whether there is any effect in using note- taking method toward listening ability at second semester at English language education faculty of teacher training and education University of Batanghari Jambi. The researcher methodology of this research was an experimental research. Which conducted the experiment class and control class. The population of the research was the second semester at English language education faculty of teacher training and education of students was 30 students consist of two classes. The experiment class (X) was 15 students and control class (Y) was 15 students as samples. The researcher gave listening test to collected data. There were two test, pretest and posttest. The formula that was used analyze the data was used T-test. The researcher found thet the pretest mean of experiment class was 58.67 and posttest mean was 79.33. the pretest mean of control class 52 and posttest mean was 68. It was found tobservation =2.323, where is ttable was 2.048 for 5%. The tobservation higher than the ttable (2.323 >2.048), so Ha was accepted while H0 was rejected. It means that there was significant effect of Note-taking method toward listening ability at second semester at English language education faculty of teacher training and education University of Batanghari Jambi.Keyword: Listening Ability, Note-taking Method.